2018
DOI: 10.15802/stp2018/129585
|View full text |Cite
|
Sign up to set email alerts
|

Research of Railway Track Parameters in the Plan Based on the Different Methods of Survey

Abstract: Purpose. The main purpose of this paper is to analyze the existing methods for surveying curves in a plan, to study the influence of the errors in measuring plan parameters on the permitted speeds of motion, to develop re-commendations for reducing road disturbances by bringing the parameters of curves to the standards that operate in Ukraine in the directions of accelerated and high-speed train traffic. The problem of restructuring the curves was not so acute until there was a need to increase the speed of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…Научная новизна. Расшире-національного університету залізничного транспорту, 2017, № 6 (72) ЗАЛІЗНИЧНА КОЛІЯ doi 10.15802/stp2017/118380 © M. B. Kurhan, D. M. Kurhan, 2017 ны подходы представления железнодорожного пути в моделях подвижного состава, описанных системами уравнений по принципу Лагранжа-д'Аламбера. Разработана методика определения характеристик железно-дорожного пути для таких моделей по результатам вариантных расчетов динамического прогиба рельса от прохождения колеса.…”
Section: представление железнодорожного пути в математической модели unclassified
See 1 more Smart Citation
“…Научная новизна. Расшире-національного університету залізничного транспорту, 2017, № 6 (72) ЗАЛІЗНИЧНА КОЛІЯ doi 10.15802/stp2017/118380 © M. B. Kurhan, D. M. Kurhan, 2017 ны подходы представления железнодорожного пути в моделях подвижного состава, описанных системами уравнений по принципу Лагранжа-д'Аламбера. Разработана методика определения характеристик железно-дорожного пути для таких моделей по результатам вариантных расчетов динамического прогиба рельса от прохождения колеса.…”
Section: представление железнодорожного пути в математической модели unclassified
“…The use of such an approach for modeling the operation of a railway track construction may take place, but for the most tasks it should be considered inappropriate. One can divide a railway track into integral objects with a constant mass on-національного університету залізничного транспорту, 2017, № 6 (72) ЗАЛІЗНИЧНА КОЛІЯ doi 10.15802/stp2017/118380 © M. B. Kurhan, D. M. Kurhan, 2017 ly conditionally. Moreover, these masses will have small displacement values, which will occur in a short period of time.…”
Section: Introductionmentioning
confidence: 99%
“…This means that this method can meet the accuracy requirement of the irregularity measurement of the high speed line [27,28]. In subsequent studies, multi sensors were used, including GNSS, inclinometer, the Inertial Measurement Unit (IMU), laser scanner and odometer, for determining railway irregularity [29][30][31][32][33]. Research has shown that GNSS measurements, which are supported by other sensors, allow one to determine track irregularity with an accuracy of less than 1 mm, and thus they meet all technical requirements in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…At other research centres, analogous studies were also undertaken to integrate tacheometric and GNSS surveys [ 26 ], with measurement support through the application of inertial navigation systems (INS) [ 27 , 28 ] or the application of mobile laser scanners [ 29 , 30 ]. In addition, studies were conducted to apply multisensor methods [ 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%